Identifying teachers' competencies in Finnish vocational education - Tapani, Annukka; Salonen, Arto O (International journal for research in vocational education and training, 2019)
Context: In Finland, vocational education has been competence-based and learner-orientated since the beginning of 2018. Teachers' work has changed because there is a need to pay more attention to students and their specific personal needs. Learning processes are planned individually and more learning options are offered in the workplace. Approach: In this article we ask the following: What kind of teachers' competencies can be identified in Finland? The metadata comprises twelve recent pieces of research on teachers' competencies in the field of Vocational Education and Training (VET) in Finland. We apply data-driven content analysis. Findings: According to our results, the work of vocational teachers included 53 separate skills comprising seven categories of competencies and three main categories of scholarships as follows: Scholarship in teaching and learning relating to pedagogy, guidance and counselling, and interaction, Scholarship in authentic learning and development referring to pedagogical leadership, partnership and innovator competency, and Scholarship in evaluation and monitoring associated with assessment. Conclusion: The work of vocational teachers in Finland has become fragmented. The fragmented work of a vocational teacher may influence the teacher's identity. The fragmented nature of the work of vocational teachers also raises the need to share expertise in educational institutions. The main challenge for teachers in vocational education in Finland is to adopt ways of authentic learning and development. (DIPF/Orig.)